G545(P) Clinical management and developing service improvement projects (sip) – our experience. (27th April 2015) - Jyothi, S; Kanani, A; Goodyear, H
Abstract : Context: Paediatric trainees have variable training in clinical management. Although all trainees are involved in audits and many in research, not many trainees understand how NHS management works. Assessment of problem and analysis of its causes: An informal discussion among senior trainees revealed that almost all were planning to attend a leadership or management course during their last year of training and specifically before attending consultant interviews. Most of these courses were oversubscribed and had trainees from different specialties leading to difficulty in following examples of change in clinical practice. Intervention: A senior trainee (ST7) liaised with the Head of School who agreed to fund this initiative for 2 years. We made enquires to other deaneries and 3 universities who organised medical management courses. We chose Keele University to collaborate with for a new bespoke course for senior paediatric trainees. The deanery allocated £30, 000 for 60 trainees to complete this course over a 2 year period. Each course was limited to 22 trainees to encourage discussion and interaction. Strategy for change: Guided by the senior trainee who initiated this project, a 4-day programme was developed on Clinical Management for paediatric trainees. Course information was disseminated via email to all senior trainees and announced in ST6–8 training days The first course was run in autumn 2012. The programme included an initial 2 days, an 8–10 week interval to complete a SIP before the final 2 days. Measurement of improvement: Feedback from 2 cohorts (42 trainees) was consistently positive with all trainees gaining insight into topics which are not usually covered during training. Having a bespoke course helped speakers to discuss examples of paediatric issues and their management. Limiting the number of trainees helped to promote discussion as intended. Effects of changes: By 2014, all level 3 trainees in our deanery had completed this course. Trainees completed a SIP and presented it to their group on the final day of the course. Trainees were encouraged to discuss their projects and offered support with the SIPs. After review of feedback, we decided to run this course yearly for the next 5 years. The deanery has encouraged trainees to improve their understanding of clinical management by providing leave and funding. This has also helped individual hospital trusts by improving clinical care due to trainees SIPs. Message for others: We feel that early exposure to knowledge of clinical management will encourage trainees to help lead change in the future.